SPE Annual Technical Conference and Exhibition 1995
DOI: 10.2118/30544-ms
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Effect of Temperature and Pressure on Wettability Using Modified Pendant Drop Method

Abstract: Wettability is a key parameter that affects the petrophysical properties of reservoir rocks. The objective of the present work is to investigate the influence of temperature and pressure on the wettability of reservoir rocks. An experimental method for the measurements of contact angle at elevated temperature and pressure has been developed, in which a Pendant Drop Interfacial Tension Cell was modified. Experimental results of contact angle and interfacial tension for two different crude oil-brine-quartz/calci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
43
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(50 citation statements)
references
References 12 publications
4
43
1
Order By: Relevance
“…As the fluid properties are dependent on system temperature and pressure (Espinoza and Santamarina 2010;Li et al 2012;Spiteri et al 2008;Wang and Gupta 1995), the examination of such a complex system at realistic conditions is highly attractive. Recent studies have shown that, as X-ray microtomography is non-invasive, it is possible to conduct experiments at representative subsurface conditions to investigate capillary trapping (Andrew et al 2013(Andrew et al , 2014cChaudhary et al 2013), measure contact angle (Andrew et al 2014b) and examine multiple points of changing capillary pressure during drainage (Herring et al 2014).…”
mentioning
confidence: 99%
“…As the fluid properties are dependent on system temperature and pressure (Espinoza and Santamarina 2010;Li et al 2012;Spiteri et al 2008;Wang and Gupta 1995), the examination of such a complex system at realistic conditions is highly attractive. Recent studies have shown that, as X-ray microtomography is non-invasive, it is possible to conduct experiments at representative subsurface conditions to investigate capillary trapping (Andrew et al 2013(Andrew et al , 2014cChaudhary et al 2013), measure contact angle (Andrew et al 2014b) and examine multiple points of changing capillary pressure during drainage (Herring et al 2014).…”
mentioning
confidence: 99%
“…The effect of pressure and temperature on reservoir rock wettability was investigated by Wang and Gupta (1995). Stock tank oil and reservoir brine from a carbonate reservoir was used.…”
Section: Contact Anglementioning
confidence: 99%
“…There is an increasing trend in IFT for the category IFT 1. Wang and Gupta (1995) concluded that the increase or decrease in IFT values depends on the composition of the brine. From categories IFT 2-5, there is a decreasing trend of IFT.…”
Section: Ift Of Brines At 90°cmentioning
confidence: 99%
“…Previous studies on the effect of temperature on IFT indicated that trends observed depended on the systems studied. [58][59][60][61][62][63] According to colloidal theory, the fluidity of the hydrocarbon chains increases as temperature increases, which allows the chains to assume more favorable packing configurations to form micelles, lowering the CMC. As temperature continues to increase, however, the thermal motion of the chains increases to the point where the close packing arrangement is disrupted, causing the CMC to increase.…”
Section: Temperature Effect On Interfacial Tensionmentioning
confidence: 99%
“…Previous studies on the effects of pressure on IFT observed that trends also depended on the system studied. [60][61][62][63][67][68][69][70][71] Experiments were conducted on aqueous CD and a dense CO 2 system at different CD concentrations (Table 3). The pressure at which experiments were conducted ranged from 800 psig to 2000 psig at constant temperature of 25ºC (77ºF).…”
Section: Temperature Effect On Interfacial Tensionmentioning
confidence: 99%